IMPLEMENTING QUIPPER SCHOOL TO ENHANCE STUDENT SELF-DIRECTED LEARNING IN BIOLOGY AT SMPK CITRA BANGSA MANDIRI KUPANG - Eci Arince Tefa; Jhon Enstein; Yonly A. Benufinit (Universitas Citra Bangsa, 2024)
This study aims to evaluate the effect of implementing Quipper School on students' learning independence in Biology subjects at SMPK Citra Bangsa Mandiri Kupang. This study uses a quantitative approach with a quasi-experimental design, involving 60 students divided into two groups: an experimental group using Quipper School and a control group using conventional learning methods. The results showed that there was a significant increase in students' learning independence in the experimental group compared to the control group, with the results of the independent t-test showing a p value <0.05 and a large effect size (Cohen's d = 0.84). The results indicate that Quipper School is resourceful as a medium for learning autonomy which enables the provision of access to materials, automatic assessment and real-time feedback features that can encourage students' autonomous studies. While this study still have weakness regarding to the generalization of its findings, it gives an implication for educators and policy makers that integrating educational technology in curriculum increases engagement. Future studies will benefit from including larger, and more diverse samples to support the generalizability of these results.